(3GdJPcQI aj HjGf CSeGA TYQGA HZOGOs - (3YHO GdbGOQCafOj GdNWjHj GdTgQGHGfj,J (B1246 (3g` s
(3ChdgG (B:s
(3ai HjGf GSeGA TYQGA HZOGO GdPjf LYd dge JPcQI aj GjGe hRGQJg GdeQMhe OGhO HGTG deG cGf hGdi HZOGO s
(3BNQgG (B:s
(3hHYO JSYI SGYGJ Jhai QMe Gddg QMeI GdGHQGQ hYeQg (B75 (3SfI s
(3HChd GdeNWhW JQLeI ddeDdas
(3cJHgG ai GjGe hRGQI GdeQMhe OGhO HGTG hGdi HZOGOs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs